Open diaphyseal fracture of the tibia in Pakistani adults: A comparative study of Plaster of Paris cast vs. Naseer Awais external fixator. - Kumar, Beesham; Bhutto, Irshad; Syed Muhammad Ali; Kumar, Ashok; Butt, Siraj Amed; Abass Memon; Ahmed Memon, Iftikhar; Yasir, Ali (International Journal of Endorsing Health Science Research, 2021)
Background: The management of open tibial diaphyseal fractures is the most challenging glitch faced by orthopedic surgeons. For open or comminuted fractures, external fixation remains the gold standard. This study aimed to assess the treatment response of fixators by comparing the results of open diaphyseal tibial fracture stabilization in adults by Plaster of Paris (POP) cast versus Naseer Awais External Fixator (NAEF). Methodology: A single-center, prospective study was conducted at the leading teaching institute and tertiary care hospital of Jamshoro and Hyderabad, Pakistan. A total of 30 patients having an open diaphyseal fracture of the tibia were randomly assigned to two groups (Group A-POP cast and Group B to NAEF; n=15 each). Duration of hospital stay and postoperative complications (like wound infection, union rate, and functional outcome) were compared between groups. Results: On average, group A patients stayed in the hospital for 3.65 weeks, while group B patients stayed for 2.49 weeks (p=0.004). Wound infections were observed in 26.7% and 53.3% of the patients in group A and B, respectively. No significant difference in the adequate callus formation (i.e. union) and good functional outcome was observed among patients of group A and B (p>0.05). Conclusion: The use of NAEF for open diaphyseal fractures of the tibia has a significant advantage over POP cast in reducing the duration of hospital stay. However, no significant differences were observed in wound infection, union rate and time, and functional outcome.